Recent Advancement for the Synthesis of MXene Derivatives and Their Sensing Protocol. Issue 10 (10th June 2021) - Abbasi, Nasir Mahmood; Xiao, Yao; Peng, Ling; Duo, Yanhong; Wang, Lude; Zhang, Li; Wang, Bing; Zhang, Han
Abstract: The highly efficient, 2D material‐based sensing devices are well‐suited with the advanced production technology which provide the data that can be applied effectively for the monitoring of environmental and health‐related problems. Recently, MXenes considered as new blood in the form of 2D transition metal carbides (TMC), transition metal nitride or transition metal carbonitrides that are added first time to 2D nanomaterials family MXene which are compounds obtained as a result of chemical delamination of quaternary or (ternary) layered nitrides or carbides found as an outstanding member of 2D elemental materials. On behalf of rich chemistries and unique morphologies, the MXenes derivatives delivered efficient sensors, energy storage, catalysis, and water purification. The superior volumetric surface area provides improved sensor response and greater optic, electrical, and magnetic characteristics, which are important advantages in biological and biomedical applications over macroscale materials. In this review article, different synthetics strategies of Mxene derivatives are organized and discuss their availability in terms of caste, yield, physical properties, and simplicity. To keep in mind, the facile synthetic approach and stable physical properties, the Ti3 C2 Tx Mxene is chosen as a model Mxene derivative, and its application in the field of environmental and biological sensors is discussed in detail. Abstract : MXene derivatives are recognized as an influential member of the 2D material community over the last decade. Because of its simple synthetic approach and stable physical properties, Ti3 C2 Tx MXene is chosen as a model MXene derivative here, and its use in the field of electrical, optical, and electrochemical based sensing materials is discussed.